PELATIHAN DAN EDUKASI TENAGA KESEHATAN DALAM PERAWATAN ANTENATAL DAN POSTNATAL BERKUALITAS SERTA KESEHATAN GIGI MULUT UNTUK PENYIAPAN GOLDEN GENERATION - Dewi, T.P.; Bayuningrat, I.G.N.M.; Pradnyaningrat, I.G.N.A.M.; Kartha, I.B.B.D. (Buletin Udayana Mengabdi, 2023)
Problems with Health Worker Partners at Rahayu Husada Clinic for Antenatal Care/ANC and Postnatal Care/PNC requiring specialist, obstetrician, and dental examinations. PKM Partnership is a solution to partner problems through quality ANC & PNC counseling and training, Dental and Oral Health which is implemented for Pregnant Women and Babies Under Two Years in preparation for the Golden Generation. Methods: outreach, focus group discussions, ANC & PNC counseling and training, dental health and mouth. At the beginning of the pretest with the results of 50% of the participants getting a score of 30, and 1% getting a score of 40, and in the posttest 39% of the participants getting a score of 70 and 80, while a score of 90 is 3%. Monitoring and evaluation through direct observation. Keywords : Antenatal Care dan Postnatal Care berkualitas, Golden Generation, Specialist Examination.